The Flavor Train: The Nature and Extent of Flavored Cigarettes in Low- and Middle-Income Countries. Issue 11 (13th May 2021) - Cohen, Joanna E; Welding, Kevin; Erinoso, Olufemi; Saraf, Sejal; Iacobelli, Michael; Smith, Katherine C
Abstract: Introduction: Flavors and depictions of flavors are attractive and facilitate initiation and use of tobacco products. However, little is known about the types of flavored products on the market, particularly in low- and middle-income countries. We describe the nature and extent of flavored cigarettes sold in nine low- and middle-income countries from four of the six World Health Organization (WHO) regions. Aims and Methods: We employed a systematic protocol to purchase unique cigarette packs in Bangladesh, Brazil, China, India, Indonesia, Philippines, Russia, Thailand, and Vietnam. Packs were double coded for flavor descriptors and imagery using a standard codebook. Frequencies and crosstabs were conducted to examine the proportion of packs with flavor descriptors and/or flavor imagery, and flavor capsules, by country and by major manufacturer. Results: Overall, 15.4% of the country-unique cigarette packs had flavor descriptors and/or imagery, representing a variety of flavors: menthol or mint (8.2%), "concept" descriptors (3.5%) (eg, Fusion blast), fruit or citrus (3.3%), beverages (1.4%), and others (1.4%). Flavor was mostly communicated using descriptors (15.2%), with flavor imagery being less common (2.2%). Flavor capsules were prevalent (6.2%), with almost half having "concept" descriptors. All major tobacco companies produced cigarettes with flavors, and with capsules. Conclusions: A range of flavored cigarettes remain on the market in the low- and middle-income countries with the greatest number of smokers. This finding is particularly concerning given the appeal of flavored cigarettes among youth and their potential to circumvent country bans on flavored tobacco products if those laws are not sufficiently comprehensive. Laws addressing flavored tobacco products need to account for flavor capsules and concept descriptors. Implications: While a number of countries have restricted flavors in tobacco products to reduce their appeal and attractiveness, a range of flavors continue to be on the market in low- and middle-income countries, putting people in these countries at increased risk for tobacco use and subsequent tobacco-caused death and disease. The presence of capsules and concept descriptors is particularly concerning given their appeal among youth and their potential to circumvent country bans on flavored tobacco products if those laws are not sufficiently comprehensive.